Influence of Plant Additives on Changes in the Composition of Fatty Acids, Lipid Quality Indices and Minerals of Fermented Dairy Products from Cow’s Milk - Beata Paszczyk; Elżbieta Tońska (Molecules)
The aim of this study was to assess the effect of selected plant additives on changes in the content of fatty acids, lipid quality indicators and mineral composition of yogurts produced from cow’s milk. The analysis included natural yogurts and yogurts enriched with 10% of chia seeds, hulled hemp seeds, quinoa seeds and oat bran. The fatty acid composition, the content of lipid quality indicators and the content of mineral components was varied in all analyzed yogurts. The plant additives used caused significant (p ≤ 0.05) changes in their fatty acid content, i.e., a significant decrease in the content of saturated fatty acids (SFAs) and short-chain fatty acids (SCFAs), and a significant increase in the content of monounsaturated fatty acids (MUFAs) and polyunsaturated fatty acids (PUFAs). The plant additives used caused significant (p ≤ 0.05) changes in the content of fatty acids, i.e., a significant decrease in the content of saturated fatty acids (SFAs) and short-chain fatty acids (SCFAs), and a significant increase in the content of monounsaturated fatty acids (MUFAs) and polyunsaturated fatty acids (PUFAs). It was shown that additives such as chia seeds and peeled hemp seeds caused the greatest changes in the analyzed yogurts. Yogurts with these additives were characterized by a significant increase in the content of polyunsaturated fatty acids (PUFAs), including n-3 acids, and a more favorable n-6/n-3 ratio. Yogurts with these additives were also characterized by significantly (p ≤ 0.05) lower atherogenic (AI) and thrombogenic (TI) indices and a higher hypocholesterolemia-to-hypercholesterolemia ratio (H/H). The addition of peeled hemp seeds caused the greatest changes in the content of minerals. Yogurts with hemp seeds were characterized by the highest content of all measured macroelements, as well as copper, iron and zinc. In turn, the highest manganese content was determined in the yogurts with the addition of chia seeds.